2022
DOI: 10.1371/journal.pntd.0010051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oseltamivir phosphate versus placebo on platelet recovery and plasma leakage in adults with dengue and thrombocytopenia; a phase 2, multicenter, double-blind, randomized trial

Abstract: Background Thrombocytopenia, bleeding and plasma leakage are major complications of dengue. Activation of endogenous sialidases with desialylation of platelets and endothelial cells may underlie these complications. We aimed to assess the effects of the neuraminidase inhibitor oseltamivir on platelet recovery and plasma leakage in dengue. Methods We performed a phase 2, double-blind, multicenter, randomized trial in adult dengue patients with thrombocytopenia (<70,000/μl) and a duration of illness ≤ 6 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Desialylation or removal of sialic acid on platelet membrane by endogenous neuraminidase, induced by binding of von Willebrand factor (VWN) to platelets, has been suggested as possible mechanism for increased platelet clearance in dengue patients [ 45 ]. Based on this, oseltamivir, a neuraminidase inhibitor that is commonly administered for influenza [ 45 ] was tested as a potential therapeutic for thrombocytopenia in a phase 2, TOTO trial (Treatment Of Thrombocytopenia with Oseltamivir in acute dengue virus infection: a randomized, placebo controlled, multicenter trial) conducted in Indonesia (ISRCTN35227717) [ 46 ]. Unfortunately, the drug was found to be ineffective for both platelet recovery and preventing plasma leakage in patients with acute dengue with moderate to severe thrombocytopenia.…”
Section: Updates In Dengue Supportive Carementioning
confidence: 99%
See 2 more Smart Citations
“…Desialylation or removal of sialic acid on platelet membrane by endogenous neuraminidase, induced by binding of von Willebrand factor (VWN) to platelets, has been suggested as possible mechanism for increased platelet clearance in dengue patients [ 45 ]. Based on this, oseltamivir, a neuraminidase inhibitor that is commonly administered for influenza [ 45 ] was tested as a potential therapeutic for thrombocytopenia in a phase 2, TOTO trial (Treatment Of Thrombocytopenia with Oseltamivir in acute dengue virus infection: a randomized, placebo controlled, multicenter trial) conducted in Indonesia (ISRCTN35227717) [ 46 ]. Unfortunately, the drug was found to be ineffective for both platelet recovery and preventing plasma leakage in patients with acute dengue with moderate to severe thrombocytopenia.…”
Section: Updates In Dengue Supportive Carementioning
confidence: 99%
“…Clinical trials for Vitamin C alone (SLCTR/2017/028) and in combination with Vitamin B1 (CTRI/2019/09/021244) are in progress Zinc Unclear mechanism Nil Randomized double-blind placebo-controlled trial ( n = 50) (TCTR20151110001) showed reduced hospitalization duration, but no improvement in other clinical or laboratorical outcomes [ 116 ] Treatment options without support for benefits Paracetamol Anti-pyretic Nil Randomized double-blind placebo-controlled trial ( n = 123) showed worse liver enzyme derangements in the treatment group, with no improvement in other clinical or laboratorical parameters. (NCT02833584) [ 20 •] Oseltamivir Neuraminidase inhibitor to block desialylation on platelet membrane One ex vivo study showed that oseltamivir reduced desialylation on platelets from healthy donors [ 45 ] Randomized double-blind placebo-controlled trial ( n = 70) did not show improvement in platelet recovery or plasma leakage parameters (ISRCTN35227717) [ 46 ] …”
Section: Development Of Therapeutics Targeting Dengue Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used plasma samples from subjects in a phase 2, double-blind, multicenter, randomized placebo-controlled trial on the effect of oseltamivir phosphate on platelet recovery and plasma leakage in adults with dengue and thrombocytopenia (ISRCTN35227717) [8]. In brief, adult dengue patients (�16 years old) with fever (� 6 days), thrombocytopenia (< 70 x10 9 /L) and positive for rapid dengue virus (DENV) non-structural protein-1 (NS1) or IgM anti-DENV (PanBio, Diagnostics, Windsor, Australia) were enrolled in six different hospitals in Central and West Java, Indonesia, between January 2018 -July 2019.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…A complete blood count was performed twice daily using a standardized hematology analyzer in each study center. Circulating albumin and syndecan-1 concentrations were determined as previously described [8].…”
Section: Clinical and Laboratory Parameter Measurementsmentioning
confidence: 99%